Interval colorectal cancer after colonoscopy - C. Teixeira; C. Martins; E. Dantas; D. Trabulo; J. Mangualde; R. Freire; A.L. Alves; I. Cremers; A.P. Oliveira (Revista de Gastroenterología de México (English Edition), 2019)
Introduction and aims: Interval colorectal cancer (iCRC) can occur due to missed lesions or to a newly developed lesion. The present study aimed to assess the iCRC rate and its characteristics in our population and find possible explanations. Materials and methods: A retrospective study was conducted on patients with colorectal cancer (CRC) diagnosed between January 2011 and January 2015 at our department. Demographics, endoscopic data, and tumor characteristics (location, histology, staging) were collected. We identified patients diagnosed with CCR who underwent colonoscopy at our department in the previous 10 years and presented the disease (iCRC) before the date of their next recommended exam. The cases of iCRC were characterized and compared with other CRC cases. Possible explanations for the appearance of iCRC were analyzed. Results: A total of 266 patients presented with CRC, 61.7% were men, and mean patient age was 70.7 years. We identified 10 patients with iCRC: 6 were men, and mean patient age was 71.1 years. Mean time for iCRC diagnosis after index colonoscopy was 3.5 ± 1.84 years. Tumor was located in the right colon in 50% of the patients with iCRC and in 24.5% of the patients without iCRC (P = .091). More patients with iCRC had a family history of CRC (50%) than the patients with reference CRC (3.1%) (P = .000). Conclusions: In our case series, 3.76% of all CRC were iCRC. There were no statistically significant differences between patients with or without iCRC, with the exception of family history of CRC. Resumen: Introducción y objetivos: El cáncer colorrectal de intervalo (CCRi) puede ocurrir debido a lesiones no detectadas o a una lesión recién desarrollada. El presente estudio tiene como objetivo la evaluación de la tasa de CCRi, de sus características en nuestra población y encontrar posibles explicaciones. Material y métodos: Estudio retrospectivo que incluye cáncer colorrectal (CCR) diagnosticado entre enero de 2011 y enero de 2015 en nuestro departamento. Se han recogido datos endoscópicos y características tumorales (localización, histología y estadificación). Se identificaron los pacientes a quienes se les realizó una colonoscopia en nuestro departamento en los 10 años anteriores al diagnóstico del CCR y que presentaron el cáncer (CCRi) antes de la fecha del próximo examen recomendado. Se llevó a cabo caracterización del CCRi comparándolo con otros CCR y analizando las posibles explicaciones para el CCRi. Resultados: Se incluyeron 266 pacientes con CCR, 61.7% varones; edad media de 70.7 años. Se identificaron 10 pacientes con CCRi: 6 varones, edad media de 71.1 años. El tiempo medio para el diagnóstico del CCRi después de la colonoscopia inicial fue de 3.5 ± 1.84 años, el tumor estaba en el colon derecho en el 50% de los pacientes con CCRi y en el 24.5% de los pacientes sin CCRi (p = 0.091). Un mayor número de pacientes con CCRi tenían antecedentes familiares de CCR (50%) en comparación con los pacientes con CCR de referencia (3.1%) (p = 0.000). Conclusiones: En nuestra serie, el CCRi representa el 3.76% de todos los CCR. No hubo diferencias estadísticamente significativas entre los pacientes con o sin CCRi, excepto los antecedentes familiares de CCR. Keywords: Interval colorectal cancer, Colonoscopy, Palabras clave: Cáncer colorrectal de intervalo, Colonoscopia